INFLUENCE OF MEN’S PARTICIPATION IN CHILDCARE TASKS ON THEIR CHILDBEARING INTENTIONS IN IBADAN NORTH LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA (2012)
Nigeria has an annual population growth rate of 2.6 and a relatively high Total Fertility Rate (TFR) of 5.6 due to its larger family size. Men’s fertility desire is a strong determinant of family sizes, but it is women that perform greater share of childcare activities. The potential relationship between the desire for childbearing and the responsibility of early childcare between spouses has not been adequately explored. This study was therefore designed to determine the extent to which the division of childcare tasks between spouses influences men’s childbearing intentions in Ibadan North Local Government Area (LGA), Oyo state Nigeria. A four-stage sampling technique was used to select 179 couples living together with their two children and whose index child was less than two years old. Data was collected from 20 communities in the LGA using a semi-structured questionnaire, which measured participation in identified childcare tasks (feeding, bathing, changing diaper-toileting, putting to bed, getting up to attend to child at night, taking child to health providers, disciplining child, paying bills), with the index child and desired family size. Men’s involvement in childcare tasks was measured on a 30-point scale. Task performance was classified as “high” >20, “average” 11-20, and “Poor” 0-10. Six Focus Group Discussions (three male and three female groups) were conducted to complement the quantitative data. Descriptive statistics, and logistic regression were used to analyse the quantitative data while the FGD data were analysed using the thematic approach. The mean ages of men and their wives were 33.5±1.5 and 28.6±5.0 years respectively. Majority of couples were married (85.7%), 94.1% were Yoruba and overall 44.2% had secondary education. Men’s mean monthly income was N24828.00±20485.00 compared with their wives N16920.00±11797.00. Men’s mean desired family size was higher (4.7±1.6) than that of their wives (4.1±1.3) as 69.5% of the men desired more than four children compared to 53.0% of the wives who had such desire. Overall, 33.0%, 46.9% and 20.1% of the women expected their husbands to perform few, some and most identified childcare tasks respectively. However, 44.7%, 36.0% and 19.3% of male respondents performed few, some and most identified childcare tasks with the index child respectively as validated by their wives. Men’s participation in childcare task, high spousal monthly income and increased spousal educational status were significantly associated with men’s desire for small family size (P<0.05). Men’s participation in childcare task (OR=2.43, C.I: 1.91-6.44) and Relegion (OR=0.278, C.I: 0.14-0.54) were strong predictors of their desired family size. Majority of FGD discussants acknowledged minimal involvement of most men in childcare activities because it increases their stress load, hence their positive inclination for large family sizes. Greater participation of men in childcare tasks decreases their desires for further childbearing. Innovative strategies for promoting male participation in childcare with a view to reducing desired family size are advocated.